The Revised Statutes of the State of Indiana, Passed at the Thirty-Sixth Session of the General Assembly; Also, Sundry Acts, Ordinances, and Public Documents Directed to be Printed Along with the Said Statutes: To Which are Prefixed the Constitution of the United States and of the State of Indiana Page 485-486 - (:unkn) unknown (General Publisher, 1852)
Granted the board of trustees for new incorporated towns to regulate the storage of gun powder and other dangerous materials.
--
Keywords: GUN POWDER STORAGE